Attribution of flood impacts shows strong benefits of adaptation in Europe since 1950 - Paprotny, Dominik; Tilloy, Aloïs; Treu, Simon; Buch, Anna; Vousdoukas, Michalis I.; Feyen, Luc; Kreibich, Heidi; Merz, Bruno; Frieler, Katja; Mengel, Matthias (Research Square, 2024)
Flood impacts in Europe are considered to be increasing, especially in connection to climate change. However, attribution of impacts to climatic and societal drivers of past floods has been limited to a selection of recent events. Here, we present an impact attribution study covering 1729 riverine, coastal and compound events that were responsible for the large majority of flood-related impacts in Europe between 1950 and 2020. We show that in most regions the magnitude of flood impacts has been regulated primarily by the opposing direct human actions. On the one hand, the population and economic value at risk have increased, exacerbated by land use change. However, it was compensated by improved risk management, manifested by better flood protection and lower vulnerability. Climate change and human alterations of river catchments were also important drivers in many regions, but ultimately less relevant for trends in total, continental-wide impacts. Overall, our study highlights the need for multidimensional impact attribution of past natural hazards. Attribution results for individual events are available on https://naturalhazards.eu/.
Gesehen am 21.05.2025